Challenges for building gender equality equality: the new constitutional rights (Revista do Tribunal Regional Federal da 3ª Região, 2015)
This article considers the failure of legal mechanisms to overcome known problems existing gender in contemporary society, characterized essentially by the contradictions arising from the creation of specific behavioral, cultural and social patterns, defined from biological sex and obligation of the individuals from birth. Starting from the assumption that changes in the specific plan does not occur concomitantly to improve the content of formal equality and formulas designed to lend it greater effectiveness, examines the need to rethink the function of law and of conceiving new mechanisms that are able to meet existing demands. On the road facing the concretion of equality, contributions offered by the theory that defends the existence of a new category of fundamental constitutional rights, called the new rights are weighted.
Keywords: equality; citizenship; challenges; new constitutional rights